Patents, technology, and commerce - Schacht, Wendy H. (Intellectual property in the 21st century (Hauppage, N.Y.), 2009)
There is an ongoing interest in the pace of U.S. technological advancement due to its influence on U.S. economic growth, productivity and international competitiveness. Because technology can contribute to economic growth and productivity increases, congressional attention has focused on how to augment private-sector technological development. This book addresses questions that have been raised concerning the proper role of the federal government in technology development and the competitiveness of U.S. industry. In response to the foreign challenge in the global marketplace, the United States Congress has explored ways to stimulate technological advancement in the private sector. Among the issues addressed in this book are whether joint ventures contribute to industrial competitiveness and what role, if any, the government has in facilitating such arrangements. This book also discusses the Bayh-Dole Act, which grants patent rights to inventions arising out of government-sponsored research and development to certain types of entities.